(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2018)
The contribution by Tommaso Edoardo Frosini offers an introduction to the essays published in the Focus that BioLaw Journal dedicates to the memory of Stefano Rodotà, who honoured our Journal accepting our invitation to take part to its Scientific Committee. Frosini’s essays recalls the main phases of Rodotà’s scientific, political and social path and serves as an introduction to the interdisciplinary contributions of the Focus.